THE RESOURCE-BASED VIEW OF THE FIRMS: IDENTIFYING UNIQUE COMPETITIVE ADVANTAGE IN TASHKENT’S START UP ECOSYSTEM - Ismoilov Elyorjon Makhamadali Ugli, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. As the Central Asian market evolves, there has been a booming digital transformation, and in this context, new institutional frameworks are required to meet local needs. This paper uses the VRIO framework to analyze startup landscape of ever-developing Uzbekistan, focusing on its digital hub in the case of Tashkent city. By elucidating competitive advantage of Tashkent city, the study focuses on the bright examples (first unicorn company “UZUM”), and the role of IT park in internalizing institutional voids (Startup Base, 2026).